Evolutionary Psychology and the Propositional-attitudes - Walter, Alex. author. aut Link
XII, 85 p. 1 illus.
Keywords: The two essays provide a critical examination of theory and research in the field of evolutionary psychology. The view advanced here is that philosophical materialism and minimalist assumptions about adaptation serve Darwinian psychology better than the more popular alternative view that relies on cognitive dualism and propositional-attitude psychology to formulate evolutionary psychology theory. A commitment to cognitive dualism is destined to undermine the physical basis of behavior upon which evolutionary theory depends. Many evolutionary psychologists do not see this but are seduced by the easy way in which hypotheses can be formulated using the ‘propositional-attitude’ model. The challenge is to develop a materialistic and mechanistic approach to understanding human cognition and behavior, including linguistic and social behavior.